CORN SEED QUALITY IN FAST INTERMITTENT AND IN CONTINUOUS DRYING WITH HIGH TEMPERATURES - El TASSA-COLODEL, Samira O.M.; AHRENS, Dirk Claudio; DONI FILHO, Luiz; BARROS, Alberto Sérgio do Rego (Scientia Agraria, 2001)
The corn seed demand has grown in the last years because of the planting expansion. The seeds come from the field with high moisture and need to be bulk dried to 13%. The drying procedure is accomplished traditionally with temperatures that do not exceed 40ºC in the drying air. The objective of this work was to study the efficiency of dryers with fast intermittent and with continuous flow in drying of corn variety seeds, using high temperatures. It was evaluated the physical, physiologic and sanitary quality of the seeds. Two lots of IAPAR 51 seed corn were submitted to two dryers: a) fast intermittent, with 60oC in the inferior camera; b) continuous flow, using 60oC (superior camera) and 50oC (inferior). The seeds samples, took during the drying process, were submitted to germination tests, cold without soil (vigor); sanity, purity and mechanical damages, in July and October of 1996. The drying speed was of 1.1 pph-1 on the continuous dryer and of 0.9 pph-1 on the fast intermittent dryer. The conclusions are: a) the fast intermittent and the continuous flow dryers are efficient in corn drying with high temperatures; b) the fast intermittent and the continuous drying does not affect the physical and physiological quality of the seeds with the 60oC and 60/50oC temperatures in the air drying, respectively; c) the Penicillium infection is not reduced with the temperatures used in the drying processes.